2007
DOI: 10.1177/156482650702800211
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on the Delivery of Animal-Source Foods to Infants and Young Children: Case Studies from Five Countries

Abstract: Background. Mexico and Peru (195 and 180 g/day, respectively) and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
29
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 30 publications
3
29
0
Order By: Relevance
“…This finding differs from that of Bandoh and Kenu [61], who found a higher level of fish consumption among children in fishing communities in Ghana, but similar to Thorne-Lyman, Valpiani et al [62]'s study of fish-farming households in rural Bangladesh where animal-source foods (fish and meat) were withheld from the diets of infants and young children. Socio-cultural practices, including gender norms, and food taboos are recognised as affecting whom within a household receives different foods, and portions thereof, and, as we found here, this can particularly affect pregnant and lactating women and young children [63]. In our study, as in Thorne-Lyman, Valpiani et al [62], cultural beliefs about the benefits and harms of fish for children were at play.…”
Section: Discussionsupporting
confidence: 68%
“…This finding differs from that of Bandoh and Kenu [61], who found a higher level of fish consumption among children in fishing communities in Ghana, but similar to Thorne-Lyman, Valpiani et al [62]'s study of fish-farming households in rural Bangladesh where animal-source foods (fish and meat) were withheld from the diets of infants and young children. Socio-cultural practices, including gender norms, and food taboos are recognised as affecting whom within a household receives different foods, and portions thereof, and, as we found here, this can particularly affect pregnant and lactating women and young children [63]. In our study, as in Thorne-Lyman, Valpiani et al [62], cultural beliefs about the benefits and harms of fish for children were at play.…”
Section: Discussionsupporting
confidence: 68%
“…At least half of the children 6 to 23 months of age in the Mexico, Peru, Haiti, and Senegal case studies had consumed an animal-source food in the previous day, whereas 27% to 51% of Ethiopian children under 36 months of age in the case study had consumed an animalsource food in the same period. 22 The median intake and density of protein was above the recommendation for all the study IYC (Tables 3 and 4). The protein intake, while meeting requirements, was from foods of poor protein quality, and there was no evidence of combining grains with pulses.…”
Section: Discussionmentioning
confidence: 78%
“…Within some cultures, taboos exist around the feeding of eggs to young children. 73 In Nepal, cultural and religious beliefs about whether foods are "hot, " "cold, " or "pollution" or have "strengthening" or "weakening" properties can play strong roles in food choices during certain stages of the life cycle, such as pregnancy and early childhood, or during recovery from illness. 38 Within the Baitadi, Brahmin, and Chhetri castes, poultry are not reared because they are believed to be unclean.…”
Section: Cultural Issues and Eggsmentioning
confidence: 99%
“…In Ethiopia, some mothers reported that eggs are good for children's health and should be fed to allow children to "grow physically and mentally strong. " 77,78 In Zimbabwe, Niger, Haiti, Peru, and Mali, eggs are thought to be good for children 73,[80][81][82] because they are rich in vitamins, they increase weight, and they make children feel good 80 or are thought to provide strength and energy and to help children grow well. 81,82 Perception of cost constraints may limit the consumption of eggs by young children.…”
Section: Cultural Issues and Eggsmentioning
confidence: 99%